Research on importance evaluation of NC machine tool working loads based on AHP-fuzzy comprehensive evaluation method. (October 2019) - Li, Guofa; Zhu, Hongxiang; Wang, Jili; Zhang, Xinge; Huo, Yongchao; Yang, Haiji
Abstract: The NC machine tool are subjected to a variety of working load during the actual machining process. The influence of different kinds of working loads on the NC machine tool's reliability level are different. Therefore, this paper proposes an importance evaluation method of NC machine tool working loads based on analytic hierarchy process (AHP) -fuzzy comprehensive evaluation to judge the influence of different kinds of working loads on the reliability level. Firstly, the hierarchical structure of the importance evaluation of NC machine tool working loads is established, and then the structure of discrimination matrix and the consistency test of the matrix are determined. Secondly, the fuzzy membership R of the fuzzy subset is established, and then the weight vector M of the evaluation factor and the evaluation result vector S of the fuzzy comprehensive evaluation are determined to realize the quantitative analysis of the fuzzy object. Finally, the importance of calculating the machining center load is ranked as cutting force, feed rate, torque, tool changing frequency, temperature and noise in the example.